Pengaruh Jumlah Penduduk Miskin terhadap Pengalokasian Belanja Pendidikan dengan Alokasi Dana Desa (ADD) dan Dana Desa (DD) Sebagai Variabel Moderating Tahun 2017 (Studi Empiris di Desa-Desa Kabupaten Wonogiri) - Rucika Dewi Febriyanti; Andy Dwi Bayu Bawono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
This study aims to analyze the influence of the Number of People Living in Poverty on the allocation of Education Expenditure, by using Village Fund Allocation (ADD) and Village Fund (DD) as the moderating variables. Based on the Law number 20/2003 on Education National System, the budget allocation for Education sector has an important role to improve the welfare of village communities in the village goverment system. The population used in this study is the entire villages (around 298 Villages) in the Wonogiri District. the purposive sampling in accordance with certain criterias was also used as a sampling method resulting to 196 villages were obtained for analysis. Multiple linear regression analysis and analysis of moderating variables were used for the examination of data. The results of this study indicate that the number of People Living in Poverty has a negatively influence to the allocation of Education Expenditure. Further, the variables of Village Fund Allocation (ADD) an Village Funds (DD) were not able to moderate the influence of People Living in Poverty on Education Expenditures.Keywords: number of people living in poverty, add, dd, and allocation of education expenditure